The Potential of Leguminous Seeds as Natural Coagulants assisted by ArduinoTM For Educational Purpose - Septiyanto, Arifin; Prima, Eka Cahya; Rusyati, Lilit; Riandi, Riandi (Scientiae Educatia: Jurnal Pendidikan Sains, 2024)
The study aims to determine the effect of variations in the concentration of tamarind and winged bean bio coagulant concentrations on turbidity sensor SKU: SENO189 and SENO244 Gravity analog TDS Sensor TDS based ArduinoTM for educational purposes. The work started with 1) the development of a measuring device with the microcontroller ArduinoTM, 2) sample preparation, and 3) sample measurement. The water quality measurement parameters are turbidity, TDS level (dependent variable), and concentration of tamarind and wingan seeds extract (independent variable). The results showed that variations in the doses of tamarind and winged bean seed extracts of 3g/0.5L, 5g/0.5L, 7g/0.5L, and 9g/0.5 reduced the turbidity and could reduce TDS values in river water. However, the most optimal dose to reduce the turbidity value and TDS value is the addition of a coagulant at a concentration of 3 g/0.5 L with a reduction in turbidity of 71.33% (tamarind seeds) and 63.17% (wingan seeds). Then the TDS reduction value was 15.58% (tamarind seeds) and 9.54% (wingan seeds). This is because tannin compounds in tamarind and winged bean seeds can precipitate protein content between molecules in peat water that do not bind to colloidal particles, forming bonds that settle quickly